The Impact of Organizational Culture and Lecturer Competence on Organizational Commitment to Influence Lecturer Performance - Permadi, I Komang Oka; Carina, Tiara; Wibawa, I Wayan Sucipta (JURNAL ADMINISTRASI & MANAJEMEN, 2023)
The aim of this study is to confirm and re-examine the effect of organizational culture and lecturer competence on lecturer performance with organizational commitment as a mediating variable. The population in this study were 61 lecturers. Samples were selected by purposive sampling and a total of 45 people were obtained. Research hypotheses were tested using path analysis with the SmartPLS version 3.2.9 application. The research results showed that organizational culture has a significant effect on organizational commitment and lecturer performance. Lecturer competence has a significant effect on organizational commitment but does not have a significant effect on lecturer performance. Likewise, organizational commitment has no significant effect on lecturer performance and organizational commitment has not been able to mediate organizational culture and lecturer competency on lecturer performance.